The Influence of Motivation, Use of Information Technology, Human Relations and Work Ethic on the Performance of Private Vocational School Heads - Achmad Rachmawan; Nani Sudiarti; Tubagus Hedi Saepudin (Dinasti International Journal of Education Management And Social Science, 2024)
This research examines the influence of motivation, use of information technology, human relations, and work ethic on the performance of heads of private vocational schools. Principals have a central role in leading schools, and these factors can influence how they carry out their leadership duties. In-depth literature studies and empirical research findings show that high motivation can increase productivity, work quality, and individual satisfaction. Effective use of information technology can support efficient school operations, better teaching, and better decision-making. Good human relations can motivate staff and students, create a positive school culture, and strengthen the principal's relationships with various stakeholders. A strong work ethic reflects commitment, dedication, and discipline on the job, which in turn influences focus, productivity, and relationships in the school environment. This research concludes that a good understanding of the influence of motivation, use of information technology, human relations, and work ethic can help private vocational school principals develop effective leadership strategies to achieve school goals and improve the quality of education.